Infant with infantile spasms: early intervention improves neurodevelopmental outcome - Narayanan, Rajeshwari; Gilbert, Aparna; Arunachalam, Savitha (International Journal of Contemporary Pediatrics, 2021)
Tuberous sclerosis complex is a multisystem genetic disorder with characteristic skin lesions and variable neurological manifestations like seizures, cognitive impairment and autistic spectrum disorder. Epilepsy and infantile spasms during first year of life are risk factors for mental impairment and Autistic spectrum disorder (ASD). In asymptomatic TSC infants, hypsarrhythmia pattern in EEG suggests early treatment with vigabatrin to improve neurodevelopmental outcome. Early recognition of skin lesions by pediatrician is crucial for timely intervention.